Mediterranean security challenges, terrorist threats and energy issues: Italy and the Libyan crisis of the 1980s - Massimo Bucarelli (The Journal of European Economic History (JEEH), 2021)
Italy's role in the Libyan-US clash caused by Muammar Gaddafi's support for international terrorism in the mid-1980s is a controversial issue whose treatment by Italian historians and scholars has been made difficult by the lack of relevant and reliable sources. This paper, based on significant documents from Giulio Andreotti's private papers, seeks to shed light on a highly critical moment for Italian foreign policy. The escalation of the Libyan-US crisis, which culminated in the armed clash in the Gulf of Sidra, the American bombing of Tripoli and Benghazi, and the Libyan missile launch against Lampedusa, overwhelmed the important political and economic initiatives that Italy had been patiently pursuing in Libya. Italy was torn between loyalty to the United States, Italy's paramount ally and a prime target of terrorist attacks, and the need to protect national strategic and economic interests in the Mediterranean region. In the end, despite the evident political and economic drawbacks, Italy had no choice but to take a stand against Libya and back the US government's hard-line policy.
Keywords: 330